Unpacking Shared Pessimism between Citizen and Bureaucracy: A Socio-Psychological Barrier to Public Service Reform in Indonesia - Fathurrahman, Reza; Hoennige, Christoph (UI Scholars Hub, 2026)
In this study, we examine the existence of a reciprocal pattern of performance bias shared between citizens and street-level bureaucrats, which we term as ‘shared pessimism’, assumed to implicate public service reform. Primary data were collected using surveys administered to 207 public service providers and 248 citizen recipients across six Indonesian public service agencies operated in two regional governments. Statistical analysis was then conducted to examine bureaucrats’ self-enhancing bias and their pessimistic view of citizen ratings, as well as to clarify citizens’ tendency to underrate the performance of bureaucrats in public service organizations. Our findings confirm pervasive internal pessimism amongst bureaucrats regarding citizen evaluations across all investigated agencies. Interestingly, however, the data reveal that both citizens and bureaucrats respectively were, in fact, not as bad as they reciprocally presumed. Finally, we demonstrate that individual bureaucrats’ beliefs on their own performance influence their propensity for change, thereby affecting the reform progress.